Monitor Kualitas Udara Berbasis Web Menggunakan Raspberry Pi dan Modul Wemos D1 - Frenki Tahir; Wrastawa Ridwan; Iskandar Zulkarnain Nasibu (Jurnal Teknik, 2020)
Air pollutant is a physical, chemical, and biological substance that can endanger the health and can cause disease in living beings. Therefore, knowledge about air quality is very important. This research aims to implement a wireless sensor network for monitoring air quality, from three different location points which are presented in the form of a website. The communication used between the client and server is the Webscoket.io communication protocol, to reduce network latency. In addition, the communication protocol works in real-time because not only the client can send a request to the server, but also can receive a response without having to send a request first. The research method used is the experimental method, which is divided into two stages namely hardware design stage and server software, microcontroller and user client design stage. The results obtained are prototyping tools used to implement wireless sensor networks for monitoring air quality using Raspberry Pi as a server and Arduino ESP-8266 as a microcontroller module. The tools have performed well as intended. In the trial, a reading of gas (CO2 and CO) sensors, temperature and humidity at the location being tested were successfully displayed on the website.